Case–control study of second‐line therapies for type 2 diabetes in combination with metformin and the comparative risks of myocardial infarction and stroke. Issue 12 (5th October 2015) - Floyd, J. S.; Wiggins, K. L.; Sitlani, C. M.; Flory, J. H.; Dublin, S.; Smith, N. L.; Heckbert, S. R.; Psaty, B. M.
Abstract : We conducted a population‐based case–control study to assess the myocardial infarction (MI) and stroke risks associated with sulphonylureas and insulin when used in combination with metformin. Cases had type 2 diabetes and used metformin + insulin or metformin + sulphonylureas at the time of a first MI or first stroke between 1995 and 2010; controls used the same treatment combinations and were randomly sampled from the same population. MI and stroke diagnoses and potential confounders were validated by medical record reviews. Compared with metformin + sulphonylurea, metformin + insulin was associated with similar risks of MI or stroke [odds ratio 0.98 (95% confidence interval 0.63–1.52)]. Meta‐analysis with another observational study improved the precision of the risk estimate [relative risk 0.92 (95% confidence interval 0.69–1.24)]. Current evidence suggests that there may not be large differences in cardiovascular risk associated with the use of insulin or sulphonylureas when used in combination with metformin.